Childhood sensorineural hearing loss and adult mental health up to 43 years later: results from the HUNT study - Mariann Idstad; Kristian Tambs; Lisa Aarhus; Bo Lars Engdahl (BMC, 2019)
Abstract Background Hearing loss is a global public health problem putting millions of people at risk of experiencing impediments in communication and potentially impaired mental health. Many studies in this field are based on small, cross sectional samples using self-report measures. The present study aims to investigate the association between childhood sensorineural hearing loss and mental health in adult men and women longitudinally in a large cohort with a matched control group, and hearing is measured by pure-tone audiometry. Studies of this kind are virtually non-existing. Methods The present study combines data from two large studies; the School Hearing Investigation in Nord-Trøndelag (SHINT) carried out yearly from 1954 to 1986, and the second wave of the Nord-Trøndelag Health Study (HUNT 2) conducted from 1995 to 1997. The participants were 7, 10 or 13 years during the SHINT, and between 20 and 56 years old during HUNT 2. The total sample consisted of 32,456 participants (of which 32,104 in the reference group). Participants with a sensorineural hearing loss in SHINT of 41 dB or more were classified with moderate-severe hearing loss (N = 66), 26-40 dB as mild (N = 66) and 16-25 dB as slight (N = 220). Mental health in adulthood was measured in HUNT 2 by symptoms of anxiety and depression, subjective well-being, and self-esteem. The association between childhood sensorineural hearing loss and adult mental health was tested by means of ANOVA. Results There was a significant relation between slight childhood sensorineural hearing loss and lowered subjective well-being in women (B = −.25, p = 0.038). Further investigation of the results revealed a significant association between slight hearing loss and symptoms of anxiety and depression (B = .30, p = 0.054) and between mild hearing loss and lowered self-esteem (B = .63, p = 0.024) among women aged 20-39 years. There were no significant relations between childhood sensorineural hearing loss and any of the three mental health outcomes among men. Conclusions This study suggests that women with slight or mild sensorineural hearing loss from childhood experience elevated levels of symptoms of anxiety and depression, lowered subjective well-being and lowered self-esteem. However, the results should be interpreted with caution due to a lack of power in some analyses.